2016
DOI: 10.1177/1525740116651251
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Eight-Step Instructional Model to Train School Staff in Partner-Augmented Input

Abstract: Augmentative and alternative communication (AAC), the supplementation or replacement of natural speech and/or writing using aided and/or unaided symbols (Lloyd, Fuller, & Arvidson, 1997), can be invaluable in helping children with complex communication needs express themselves in the classroom. However, providing the appropriate piece of technology alone does not ensure successful communication (Douglas, 2012). Rather, the success of a communication interaction between an AAC user and a communication partner w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These teachers and classroom staff members are well-positioned to dramatically increase access to aided AAC and communication interventions for the population of students with extensive support needs. When provided with training in well-defined, research-based practices, teachers, and other classroom staff can provide effective communication instruction (Binger et al., 2010; Clendon & Anderson, 2016; Kent-Walsh et al., 2015; Senner & Baud, 2017). Helping these educators acquire the knowledge, skills, dispositions, and resources required to provide symbolic communication intervention throughout the school day has the potential to dramatically improve communication outcomes for students with extensive support needs and complex communication needs.…”
Section: Access To Communication Interventionmentioning
confidence: 99%
“…These teachers and classroom staff members are well-positioned to dramatically increase access to aided AAC and communication interventions for the population of students with extensive support needs. When provided with training in well-defined, research-based practices, teachers, and other classroom staff can provide effective communication instruction (Binger et al., 2010; Clendon & Anderson, 2016; Kent-Walsh et al., 2015; Senner & Baud, 2017). Helping these educators acquire the knowledge, skills, dispositions, and resources required to provide symbolic communication intervention throughout the school day has the potential to dramatically improve communication outcomes for students with extensive support needs and complex communication needs.…”
Section: Access To Communication Interventionmentioning
confidence: 99%
“…This issue is not only mentioned in relation to Malaysia (Mohd Hanafi et al, 2020) but also reported in Brazil (Nunes & Walter, 2020), Saudi Arabia (Rashed Aldabas, 2019, and Sri Lanka (Ketheeswaran, 2019). One of the most common factors reported as leading to this phenomenon is inadequate training for preservice and in-service teachers; it was found that special education teachers have minimum access to teacher professionalism related to AAC (Senner & Baud, 2017;Tonsing & Dada, 2016).…”
Section: Introductionmentioning
confidence: 99%